Study Tokoh Kepemimpinan Prof.Dr. Mahmud Yunus Pada Lembaga Pendidikan Islam di Indonesia - Nur, Khairanis (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study is motivated by the figure of Prof. Dr. Mahmud Yunus, a prominent scholar in Islamic education known for his educational concepts and his role as a pioneer of Islamic education in Indonesia. He has played a significant role in shaping the concept of Islamic education. The purpose of this research is to examine the concepts and leadership styles practiced by Prof. Dr. Mahmud Yunus, who is regarded as one of the pioneers of Islamic education in Indonesia. The research employs a library research approach, which involves gathering data and information from resources available in libraries, such as documents, historical accounts, and books related to the subject figure. The methodology used is qualitative, focusing on describing the leadership concepts and styles of Mahmud Yunus. The data sources include primary and secondary materials, obtained from interviews with alumni and written works about Mahmud Yunus. The findings reveal that Mahmud Yunus demonstrated a leadership concept that embodies noble character, visionary thinking, confidence, a foundation of knowledge and faith, integrity, creativity, and innovation. His leadership style reflects qualities such as fathanah (wisdom), amanah (trustworthiness), siddiq (truthfulness), and tabligh (effective communication). Furthermore, his leadership style is transformational, which makes it highly ideal and applicable across different times. Even today, his leadership principles continue to serve as a timeless reference and guide.